Designing, Testing and implementing a Technology-based and improved leave administration system at the UP Human resource Development Office - Lectura, Leizel (University of the Philippines Diliman, 2015)
Human Resources Development and Benefits Division (HRDBD) of the Human Resources Development Office (HRDO) aims at provision of responsive and excellent development and administration of effective human resource management service among all UP employees. Its goal is to establish realistic, systematic, efficient, and easy to follow policies and procedures.